The village time in a new cognitive framework - Vukićević, Slobodan (Sociološki pregled, 2022)
The sociological cognitive framework of analyzing and interpreting the village time is founded on the trilogy of human, man‘s and humanity time. The general theoretical approach is specified on the village time with the sovereignty of human time, peasant‘s (man‘s) time and the village community (humanity) time. All three types of time have special roles, functions, importance, meaning and sense in the constitutive and regulatory establishment of the method of production of the village and social life on the whole. In their interference, the energy is manifested of the absolute zero point of the social universe time, as man‘s – social time. The work sketches an ideal-type form of the village time, which can be only a theoretical-methodological means revealing logos assumptions of the positive correlation of the human, peasant‘s and village community time. Such ideal-type form of the village of time has a cognitive and practical character. The cognitive one implies discovering the symmetry of human, peasant‘s and humanity time of the village community, and the causes of the appearance of asymmetry. The practical one implies the construction of a constitutive and regulatory structure of the social system of a certain society and the place and role of the village community in that society, with the aim of achieving progress as the fulfilment of fundamental human needs.
Keywords: human time; peasant‘s (man‘s) time; the village community time (humanity time); logos valence; interference; ideal-type form